Bifunctionalized conjugated microporous polymers for carbon dioxide capture. (20th March 2015) - Zhang, Chong; Yang, Xiao; Zhao, Yang; Wang, Xiaoyan; Yu, Miao; Jiang, Jia-Xing
Abstract: A novel kind of bifunctionalized conjugated microporous polymers containing sultone and hydroxyl groups has been synthesized via palladium-catalyzed Sonogashira–Hagihara cross-coupling reaction of bromophenol blue with 1, 4-diethynylbenzene or 1, 3, 5-triethynylbenzene. The resulting polymers show high specific surface area up to 1470 m 2 g −1 and good thermal stability.BFCMP-2 exhibits a hydrogen uptake ability of 156 cm 3 g −1 (∼1.39 wt%) at 77 K/1.13 bar and a carbon dioxide uptake capacity of 2.77 mmol g −1 at 273 K/1.13 bar. Compared with most other reported non-functionalized conjugated microporous polymers, both of the bifunctionalized polymer networks show relatively high isosteric heat of CO2 adsorption (25 kJ mol −1 ) due to the introduction of the polar functional groups of sultone and hydroxy enhanced the binding affinity between the polymer networks and CO2 molecules. The results demonstrate that the introduction of strong polar groups into a polymer skeleton is an efficient strategy to produce CO2 -philic microporous organic polymers with enhanced binding affinity with CO2 molecules. Graphical abstract: Highlights: Bifunctionalized conjugated microporous polymers (BFCMPs) have been synthesized. The BFCMPs show high surface area up to 1470 m 2 g −1 . The BFCMPs show carbon dioxide uptake capacity of 2.77 mmol g −1 at 273 K/1.13 bar.